Effectiveness of Vascular Catheter Removal Versus Retention in Non-ICU Patients with CRBSI or CABSI in Retrospective, Single-Center Study - Giovanni De Capitani; Marta Colaneri; Claudia Conflitti; Fabio Borgonovo; Lucia Galli; Giovanni Scaglione; Camilla Genovese; Rebecca Fattore; Monica Schiavini; Beatrice Caloni; Daniele Zizzo; Nicola Busatto; et al. (Microorganisms)
Catheter-associated bloodstream infections (CABSIs) and catheter-related bloodstream infections (CRBSIs) are significant causes of morbidity and mortality worldwide. The current practice favors the removal of vascular access devices (VADs); however, the evidence on this topic remains inconclusive. This study evaluates the clinical outcomes in terms of in-hospital mortality and catheter retention vs. removal in CABSI and CRBSI cases. A retrospective, observational, single-center study was conducted at Luigi Sacco Hospital, Milan, Italy (May 2021–December 2023), and it analyzed non-ICU adult patients with VADs diagnosed with CRBSIs or CABSIs. Clinical and microbiological data were collected to assess the outcomes based on catheter management. Among 1874 patients with VADs, 147 were included, with 164 VAD infection events (92 CABSIs and 72 CRBSIs). Overall, 35 (23.8%) patients with CABSIs and CRBSIs died. Out of those who retained the catheter 19 (35.8%) patients died, while among removal patients 16 (17%) died (p = 0.018). A Candida spp. isolation was found to be significantly associated with a higher likelihood of catheter removal (p = 0.04). Our findings suggest that, in non-ICU CRBSI and CABSI cases, VAD removal may be associated with improved outcomes when feasible.